Pertumbuhan Bibit Trembesi (Samanea saman Merr.) Pada Media Tailing Dengan Penambahan Arang Sekam Dan Pupuk Kompos - Basuki Wasis; Amriliadi Bintang Sopandi (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2021)
Gold mining is a kind of open pit mines that produce waste in the form of toxic tailings. Before being returned to the environment, tailings should be through the treatment process to eliminate chemical properties that are harmful. After missing the toxicity of the tailings can be returned to the environment, but this type of land is not good for plant growth. Therefore require additional treatment so that plants can grow on media tailing. One way is by adding organic matter such as husk and compost. Besides the selection of plants also need to be considered, the type of plants that should be planted is the kind of fast growing species like trembesi (Samanea saman Merr). This study aims to examine the provision of husk and compost on the growth of trembesi seeds in the tailing media. The experimental design used in this study is completely randomized factorial design with two factors, namely husk and compost. The result showed that administration of husk and compost singly no real effect on all parameters observed. Interaction addition of these two factors was not significant on height and diameter parameters, but the real effect on the parameters of total wet weight and total dry weight. Keywords: compost, husk, open pit mining, tailing, trembesi